Strategi Campaign “Smiling West Java” dalam Meningkatkan Pariwisata Kebudayaan dan Ekonomi Kreatif - Bagas Hagy Prasetio; DADAN MULYANA (UNISBA Press, 2022)
Abstract. One of the Government Offices in Indonesia, namely the West Java Province Tourism and Culture Office, in December 2019 held a